ANALISIS PERUBAHAN SOSIAL DAN BUDAYA MASYARAKAT PEGUNUNGAN SEBAGAI DAMPAK DARI GLOBALISASI - Fikaanjana_16; Faisol Hakim (Madani : Journal of Social Sciences and Social Science Education, 2024)
Globalization is a phenomenon that involves connections between nations in various aspects of life, such as changing the economics and technology, social structures and cultural values throughout the world. These changes can be seen in social relationship pattern between others that occur in Indonesian villages, the local traditions that were previously collective and deep are changed becoming individualism through the media and global connectivity. Globalization causes various problems in the field of culture, for example: loss of the original culture of a region or village, the erosion of cultural values, decreased sense of nationalism and patriotism, loss of kinship and mutual relationship, loss of self-confidence, lifestyles that are not in accordance with customs. So that education can become a driving force for positive change without eliminating the cultural identity of local communities. The approach used in this research is a qualitative with phenomenology type. This research is located in Gununggeni village, Probolinggo district. The results of this research explained that there have been significant changes in Gununggeni Village as the impact of globalization and modernization which changed various aspects of people's lives, including lifestyle, values and economic structure. This change includes in fashion, food, technology, and social values. The use of mobile phones access to social media, and the changes in business infrastructure are strong indicators of modernization in the village. Even though there is adaptation to global trends, traditional values such as mutual relationship with other and togetherness are still strongly maintained in Gununggeni Village. This is one of social change complexity taking place, where some of traditional values are still exist, but while others becoming change.